Pengaruh Pemberian Enzim Fitase pada Pakan untuk Meningkatkan Performa Ternak Babi - Yustina Rince Wadun; Sabarta Sembiring; Tara Tiba Nikolaus (Lembaga Pengembangan Kinerja Dosen, 2025)
The study, conducted in Tilong, aimed to collect data on pig farming. The study materials included phytase, wet pig manure, dry pig manure, pig manure diluted with distilled water, individual pig pens, and 16 fattening pigs. This study used a completely randomized design (CRD), with 16 fattening pigs in each group, and each group was replicated four times. P0 was the basal diet (control group), P1 was supplemented with phytase at 1000 units/kg of feed, P2 with 1500 units of phytase/kg of feed, and P3 with 2000 units of phytase/kg of feed. The content of porcine polysaccharides (PBB) was also measured. Variables: PBB, feed intake, and feed conversion. Analysis of variance (ANOVA) was used to evaluate all measurements. If significant differences were found, Duncan's multiple comparison test (DMRT) was used for further evaluation. The results showed no significant differences between feed conversion ratio, feed intake, and multiple bacterial colony formation rate (PBB) (P>0.05). Therefore, phytase addition at various levels did not significantly improve feed conversion ratio and PBB. The optimal enzyme addition was 1,500 units of phytase per kilogram of feed. This study concluded that further research could be conducted by increasing the enzyme addition level.